Advancing Beach Tourism: The Role of Smart Technology in Enhancing Attractiveness - Govekar , Supriyanka; Dayanand, M.S; DSouza, Edgar (Turizam, 2025)
This study explores the implementation of Smart Beach Parameters in Goa’s tourism industry to enhance the beach experience and support effective management and planning. As tourism evolves globally, the integration of information and communication technologies (ICT) is crucial for sustaining competitiveness and promoting sustainable development. The research aims to develop a tailored Smart Tourism Destination Scale for Goa, focusing on five key factors—Amenities, Accessibility, Activities, Available Packages, and Ancillary Services—and their impact on the Attractiveness of beach destinations. A mixed-method approach, including a primary field survey, semi-structured interviews, participatory observation, and data analysis through SPSS, was employed to assess the significance of these factors. Findings indicate that Amenities, Accessibility, and Activities are pivotal in enhancing beach attractiveness, while Available Packages and Ancillary Services contribute to overall tourist satisfaction. The results provide practical insights for improving beach tourism management in Goa, offering a framework for integrating smart solutions that can attract both domestic and international tourists. The implications emphasize the need for dynamic technological platforms to improve beach management and tourist experiences. Future research is recommended to validate the developed scale using Confirmatory Factor Analysis (CFA) and explore the integration of emerging technologies like AI, AR, and VR. This study contributes to the theoretical understanding of smart tourism and provides actionable recommendations for enhancing the sustainability and competitiveness of beach destinations.
Keywords: Smart Beaches; Tourism Management; Smart Tourism Destination Scale; Sustainable Development; Beach Tourism